Prinsip-Prinsip Pengembangan Kurikulum PAI Pada Kurikulum Merdeka : A Systematic Literature Review - Erihadiana, Mohamad; Hakiki, Kiki Miftahul; Azizah, Habibah Nur; Maulana, Ahmad Nanda; Nasution, Fahren Sepujan (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study examines the principles of curriculum development in Islamic Education within the Merdeka Curriculum through a Systematic Literature Review (SLR). Literature was retrieved from Google Scholar using the Publish or Perish application and analyzed following the PRISMA framework. Of the 986 records identified, six studies met the inclusion criteria and were synthesized. The findings identify six core principles of curriculum development: orientation toward the goals of Islamic education, relevance to contemporary developments, integration of Islamic values across curriculum components, student-centered learning, flexibility and adaptability, and a comprehensive and holistic approach. The review also reveals that curriculum development is influenced by educational policy, technological advancement, philosophical and psychological foundations, sociocultural context, globalization, religion, and economic conditions. These findings provide a conceptual framework for strengthening the implementation of the Merdeka Curriculum in Islamic Education.